Sectoral investment analysis for Saudi Arabia. Issue 38 (15th August 2022) - Javid, Muhammad; Hasanov, Fakhri J.; Bollino, Carlo Andrea; Galeotti, Marzio
ABSTRACT: This study aims to investigate the determinants of short- and long-run private investment behavior in Saudi Arabia for eight non-oil sectors. Saudi Arabia is currently proceeding with its Vision 2030 reform plan, which aims to significantly increase the private sector's contribution to the country's gross domestic product. Thus, analyzing private investments at the sectoral level is important for Saudi Arabia. Such an analysis can provide policymakers with a deeper understanding of potential opportunities for boosting private sector growth. This study therefore uses a cointegration and equilibrium correction approach to empirically analyze investments by sector over the period from 1989–2017. We identify a long-run relationship among investments, output and the real interest rate for all sectors except agriculture. Additionally, the real exchange rate has long-run relationships with investments in the agriculture, non-oil manufacturing and other services sectors. This finding implies that sector-specific tailored investment policies are preferable to a one-size-fits-all investment policy.